Phenotypic Expression, Natural History, and Risk Stratification of Cardiomyopathy Caused by Filamin C Truncating Variants. Issue 20 (16th November 2021) - Gigli, Marta; Stolfo, Davide; Graw, Sharon L.; Merlo, Marco; Gregorio, Caterina; Nee Chen, Suet; Dal Ferro, Matteo; PaldinoMD, Alessia; De Angelis, Giulia; Brun, Francesca; Jirikowic, Jean; Salcedo, Ernesto E.; et al.
Abstract : Background: Filamin C truncating variants ( FLNCtv ) cause a form of arrhythmogenic cardiomyopathy: the mode of presentation, natural history, and risk stratification of FLNCtv remain incompletely explored. We aimed to develop a risk profile for refractory heart failure and life-threatening arrhythmias in a multicenter cohort of FLNCtv carriers. Methods: FLNCtv carriers were identified from 10 tertiary care centers for genetic cardiomyopathies. Clinical and outcome data were compiled. Composite outcomes were all-cause mortality/heart transplantation/left ventricle assist device (D/HT/LVAD), nonarrhythmic death/HT/LVAD, and sudden cardiac death/major ventricular arrhythmias. Previously established cohorts of 46 patients with LMNA and 60 with DSP -related arrhythmogenic cardiomyopathies were used for prognostic comparison. Results: Eighty-five patients carrying FLNCtv were included (42±15 years, 53% men, 45% probands). Phenotypes were heterogeneous at presentation: 49% dilated cardiomyopathy, 25% arrhythmogenic left dominant cardiomyopathy, 3% arrhythmogenic right ventricular cardiomyopathy. Left ventricular ejection fraction was <50% in 64% of carriers and 34% had right ventricular fractional area changes (RVFAC=(right ventricular end-diastolic area – right ventricular end-systolic area)/right ventricular end-diastolic area) <35%. During follow-up (median time 61 months), 19 (22%) carriers experienced D/HT/LVAD, 13 (15%) experienced nonarrhythmic death/HT/LVAD, and 23 (27%) experienced sudden cardiac death/major ventricular arrhythmias. The sudden cardiac death/major ventricular arrhythmias incidence of FLNCtv carriers did not significantly differ from LMNA carriers and DSP carriers. In FLNCtv carriers, left ventricular ejection fraction was associated with the risk of D/HT/LVAD and nonarrhythmic death/HT/LVAD. Conclusions: Among patients referred to tertiary referral centers, FLNCtv arrhythmogenic cardiomyopathy is phenotypically heterogeneous and characterized by a high risk of life-threatening arrhythmias, which does not seem to be associated with the severity of left ventricular dysfunction. Abstract : Supplemental Digital Content is available in the text.